Comparative study between histological changes in placenta from pre-eclampsia cases and normal pregnancy with special reference to cytotrophoblastic cell hyperplasia, villous stromal fibrosis and fibrinoid necrosis - Sahay, Bhawana; Talukdar, Leena; Sahay, Pallavi; Datta, Debashish; Chaubey, Rangnath (International Journal of Research in Medical Sciences, 2016)
Background: Placenta is a vital organ and the most accurate record of the infant’s prenatal experience. Pregnancy complications like hypertension significantly affect the placenta. Thus there is a need for thorough examination of it. Therefore the present study is dedicated to see the histological changes in placenta of pre-eclampsia with special reference to cytotrophoblastic cell hyperplasia, villous stromal fibrosis and fibrinoid necrosis and compared it with that of normal placenta. Methods: Total 60 placentas were collected (30 from pre-eclampsia and 30 from normal pregnancy). Results were expressed in percentage after counting 100 villi. Data analysis has been done using Graphpad InStat 3 version and data is significant when p – value is <0.05. Results: Mean no. of cytotrophoblastic cell hyperplasia, villous stromal fibrosis and fibrinoid necrosis in normal placenta are 10.1±5.01, 2.26±1.56 and 2.84±1.4 respectively and those in pre-eclampsia placenta are 36.82±16.15, 28.16± 34.42 and 8.22±1.44 respectively which are highly significant ( p-value <0.001). Conclusions: There is significant increase in number of cytotrophoblastic cell hyperplasia, villous stromal fibrosis and areas fibrinoid necrosis in placenta from pre-eclampsia cases than that of normal placenta. These changes may be due to vascular insufficiency which is usually occurring in pre-eclampsia.